Impact of Buyout Programs on Land Use Patterns in the Special Flood Hazard Area of Pitt County, North Carolina - Adeniji, Kayode Nelson (East Carolina University, 2023)
The buyout program is a voluntary action by property owners that involves selling their properties after a disaster (such as Hurricane Floyd) to the government and relocating outside the flood hazard risk area. This study examines how buyout parcels affect adjoining properties in the Special Flood Hazard Area. The study adopts a mixed-method approach involving quantitative and qualitative data collection and analysis. Quantitative aspects include geospatial data acquisition and analysis using descriptive statistics and geographically weighted regression (GWR). The qualitative approach includes semi-structured interviews with key informants and data analysis using descriptive and thematic coding. This research identified 418 buyout parcels in the study area between 2000-2021. Almost 97% (404) of the parcels are in the special flood hazard area (SFHA). All 418 parcels have been converted into different land uses, including parks, trails, wetlands, and open spaces. The GWR results show that the buyout parcels only explain 5.76% of the SFHA remaining parcels' land value. Further consideration of other explanatory variables, such as parcel size, proximity to school, rescue location, etc., increased the adjusted R2 from 0.0576 to 0.522, which means that the combination of these variables explains 52.2% of the land value in the SFHA. Study results identified that the buyout timeframe and maintenance cost of buyout parcels were key challenges to the county and the adjoining property owners. This study recommends increasing funding streams to maintain or convert the buyout parcels to the Federal Emergency Management Agency's recommendations, such as parks, bike/hike trails, etc.
Keywords: Buyouts; Land use--North Carolina--Pitt County--Planning; Government purchasing of real property--North Carolina--Pitt County